Protocol for long-term ex vivo cultivation and imaging of Drosophila imaginal discs - Liyuan Sui; Christian Dahmann (STAR Protocols)
Summary: Drosophila wing and eye-antennal imaginal discs are excellent models for studying tissue development and cell behavior. Here, we present a protocol for long-term cultivation and imaging of wing and eye-antennal imaginal discs. We describe the mounting, dissection, and ex vivo cultivation of imaginal discs. We further detail 4D time-lapse image acquisition with minimized phototoxicity and image restoration using a machine-learning-based algorithm. This protocol is suitable for studying dynamic cell behaviors with single-cell resolution during normal and perturbed development.For complete details on the use and execution of this protocol, please refer to Sui and Dahmann.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.